Gradient doping of copper in ZnO nanorod photoanode by electrodeposition for enhanced charge separation in photoelectrochemical water splitting - Rasouli, Fatemeh; Rouhollahi, Ahmad; Ghahramanifard, Fazel (Superlattices and microstructures, 2019)
New and improved electrochemical synthetic approaches have been developed to improve the photoelectrochemical performance of ZnO nanorods by homogenous and gradient doping of copper. The ZnO, Cu-doped ZnO, ZnO Cu-doped ZnO homojunction and also Cu gradient doped ZnO photoanodes were electro-synthesized and characterized by X-ray diffraction, scanning electron microscopy, energy-dispersive X-ray spectroscopy and UV–visible absorption spectroscopy. A comparative study was done between samples and Cu gradient doped ZnO photoanodes exhibit significantly enhanced photocurrent density in photoelectrochemical cell applications as compared to other photoanodes. By comparing the results, it is found out that the homogeneous Cu-incorporated ZnO photoanodes show an enhanced photoelectrochemical response, but not as well as Cu gradient doped ZnO photoanodes. The photoelectrochemical performance improvement by adjusting the copper concentration profile is attributed to an extra charge separation effect. The linear sweep voltammetry, electrochemical impedance spectroscopy and Mott-Schottky analysis were used to confirm the improved charge separation. [Display omitted] •Electrodeposition of Cu gradient doped ZnO and ZnO/Cu-doped/ZnO homojunction photoanodes.•Effective charge separation and low charge recombination rate in Cu gradient doped ZnO.•Visible light performance of Cu gradient doped ZnO.•Enhanced PEC response of homogeneous Cu-incorporated ZnO photoanodes toward water splitting.